Cerebral Perfusion in Pediatric Stroke: Children Are Not Little Adults. Issue 5 (October 2021) - Lee, Sarah; Jiang, Bin; Heit, Jeremy J.; Dodd, Robert L.; Wintermark, Max
Abstract : Abstract: Cerebral perfusion imaging provides useful information about the hemodynamic state of the brain that is relevant to a number of neurologic conditions, including stroke, epilepsy, and brain tumors. Multiple imaging modalities have been developed to evaluate brain perfusion, primarily by the use of different tracers to measure cerebral blood volume and cerebral blood flow. Here, we provide an overview of magnetic resonance imaging perfusion techniques; summarize the role of perfusion imaging in adult stroke; describe changes in cerebral blood flow over childhood; and discuss the relevance and future directions of perfusion imaging in pediatric cerebrovascular disorders and stroke.